Input-output analysis with linear programming: The case of Turkey - (:unkn) unknown (My University, 2012)
Economic planning is a vital tool for countries to achieve socio-economic goals and objectives, which can be expressed quantitatively. Input-output analysis and linear programming techniques are convenient and efficient methods for economic planning, that is why they are being used in a widespread manner. Input-output analysis is based on examining input-output table which reflects the all goods, services and the sectoral relationships in an economy particularly. Input-output model is a consistency model and it does not deal with the matter of optimal resource allocation. For that reason, there is in need of an optimization technique. In this study, Linear Programming techniques are used, because some applicable economic assumptions give way to express all the sectoral relationships linearly. In this context, it is useful to implement both Input-output analysis and Linear Programming techniques to obtain the most effective and consistent results. The purpose of this study is to determine the optimal distribution of economic resources on sectoral basis to maximize the national income. In this sense, the economic structure of Turkey is investigated and the sectoral production levels are specified with Linear Programming techniques by using the latest input-output table, which is organized by Turkish Statistical Institute for the year 2002. © EuroJournals Publishing, Inc. 2012.
Keywords: Input-output analysis; Linear programming